Community-Partnered Training in Trauma-Informed Primary Care for Patients Experiencing Reentry From Incarceration: A Pilot Training Study - Lauren E. Szkodny; Mahlet A. Yared; Shoshana H. Bardach; Joseph Lascaze; Randy Stevens; Anna M. Adachi-Mejia; Milan F. Satcher (Journal of Primary Care & Community Health)
Introduction/Objectives: Patients returning to the community from incarceration (ie, reentry) are at heightened risk of experiencing trauma when interacting with the healthcare system. Healthcare professionals may not recognize patients’ trauma reactions or know how to effectively respond. This paper describes the development and pilot evaluation of a single-session training to prepare primary care teams to deliver trauma-informed care (TIC) to patients experiencing reentry. Methods: A multidisciplinary team including community members with lived experience engaged in a multiphase human-centered design process that incorporated interviews, discussions, and a participatory process to design and evaluate a single-session interactive pilot training targeting providers’ attitudes toward formerly incarcerated patients and confidence to deliver TIC. Results: Both pre- and post-training surveys were completed by 12 TIC training attendees, which included primary care providers and staff. Trainees reported significant increases in confidence to reduce potentially re-traumatizing practices and improved attitudes toward formerly incarcerated individuals. They also expressed interest in receiving additional TIC training and learning how best to care for and meet the needs of persons with a history of incarceration. Trainees described the panel of community members with lived experience as one of the most rewarding aspects of the training. Conclusion: Centering people with lived experience in the training design and delivery produced a single-session TIC training that was both well-received and effective. Our TIC training helped primary care providers and staff move from being merely informed on trauma to having the self-efficacy to prevent and respond to trauma reactions during encounters with all patients, particularly those with a history of incarceration.